2023
DOI: 10.1002/kjm2.12650
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine promotes ferroptotic cell death in gastric cancer via hsa_circ_0008035/miR‐302a/E2F7axis

Abstract: Dexmedetomidine (DEX), a common anesthetic, has significant effects on the biological features of cancer cells. Although numerous studies have been published on the impact of DEX on the biological characteristics of GC cells, the mechanism remains unknown. This study aimed to explore the effect of DEX on the biological properties of GC cells. DEX suppressed the viability and increased the apoptosis of GC cells in vitro and inhibited tumor growth in vivo. Besides, DEX raised the levels of reactive oxygen specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 34 publications
0
6
0
1
Order By: Relevance
“…Gao et al found that circ0008035 increased E2F transcription factor 2 (E2F2) expression by acting as a ceRNA for miR-302a. Circ0008035 inhibited dextromethorphan-induced ferroptosis, and overexpression of miR-302a or knockdown of E2F transcription factor 7 (E2F7) effectively reversed this effect ( Gao and Wang, 2023 ). In other words, circ0008035 can affect ferroptosis regulation of tumorigenesis through two independent parallel pathways, which provides a viable therapeutic option for gastric cancer.…”
Section: Ferroptosis Related Circrna Involvement In Regulating Cancer...mentioning
confidence: 99%
“…Gao et al found that circ0008035 increased E2F transcription factor 2 (E2F2) expression by acting as a ceRNA for miR-302a. Circ0008035 inhibited dextromethorphan-induced ferroptosis, and overexpression of miR-302a or knockdown of E2F transcription factor 7 (E2F7) effectively reversed this effect ( Gao and Wang, 2023 ). In other words, circ0008035 can affect ferroptosis regulation of tumorigenesis through two independent parallel pathways, which provides a viable therapeutic option for gastric cancer.…”
Section: Ferroptosis Related Circrna Involvement In Regulating Cancer...mentioning
confidence: 99%
“…По данным предсказательных алгоритмов in silico (https://mirdb.org), miR-302_3P и miR-520_3P таргетируют мРНК ранее упомянутых регуляторов клеточного цикла TFAP4 и E2F2, а также рецептор витамина D (VDR). Экспериментальные данные подтверждают способность miR-302 ингибировать экспрессию мРНК TFAP4 и E2F2 [43,44], а miR-520 -экспрессию мРНК E2F2 [45]. Таким образом, наблюдаемое при активации макрофагов понижение экспрессии мРНК TFAP4 и E2F2 может быть следствием активности мкРНК.…”
Section: вклад посттранскрипционных механизмов в понижение уровней мрнкunclassified
“… 28 , 30–32 , 34 , 39 Furthermore, DEX was shown to promote oxidative stress and iron production in human gastric carcinoma cells leading to the induction of ferroptotic cell death. 38 , 40 , 41 In addition, DEX impairs cellular migration by decreasing vimentin expression and increasing the adherence of tumor cells via increased expression of E-cadherin. Moreover, DEX inhibits the proliferation of malignant cells by provoking cell cycle arrest via a decrease in cyclin D1 expression.…”
Section: Introductionmentioning
confidence: 99%
“… 33 DEX regulates circular RNAs, thereby affecting the circ -0003340/miR-198/HMGA2 35 and circ0008035/miR-302a/E2F7 axes. 38 Moreover DEX reduces the expression of the long non-coding RNA metastasis-associated lung adenocarcinoma transcript 1 (MALAT1), thus reducing cellular viability in vitro and decreasing tumor growth in vivo 36 ( Figure 3 ). Taken together, these recent data argue that DEX could also mediate direct anti-tumor effects through a variety of mechanisms including epigenetic modifications, the induction of apoptotic and ferroptotic cell death, 42 a decrease in tumor cell migration via the expression of E-cadherin and the depletion of vimentin, and an arrest in cell cycle through the cessation of cyclin D1 synthesis.…”
Section: Introductionmentioning
confidence: 99%